In depth analysis of patients attending in a tertiary care hospital due to animal injuries: A major public health problem - Mandal, Nilay; Kuiri, Shib Shankar; Sharma, Yash; Ghosh, Pranab Kumar; Kumar, Purushottam; Nandi, Mintu Mohan (Asian Journal of Medical Sciences, 2017)
Background: Injuries and illnesses from animal encounters continue to be a major public health problem. Many injuries remain undocumented and increases mortality before receiving adequate medical care specially in tertiary care setup. Key of management is to increase awareness and knowledge regarding human-animal relationship, prevention and primary treatment of such injuries. Aims and Objectives: 1) To evaluate vulnerable age and sex affected by animal injury.2) To evaluate which body parts are most injured in which type of animal. 3)To evaluate type of surgical intervention required. Materials and Methods: All patients admitted or treated due to animal injuries in the Department of General Surgery, B.S. Medical College and Hospital, Bankura, West Bengal during July,2011 to December,2012. Unwilling patients, patient with aquatic animal injury and who expired on spot or before admission were excluded from study. Results: Total of 59 patients were included in this study, with 69% of them are male, mean age of presentation was 31years and the commonest age group being 3rd decade. Most of the incidence occurs in villages i.e. 90% and mainly injured by dogs 37% followed by cows 29%. Conclusion: Domestic animals like bull, cow and dog can cause various types of injuries and management is a challenge for surgeon who needs to assess the injury and take a call on type of management. Among various types of injuries, perineal injuries are still a paramount for management due to its complex anatomy and less accessibility. Early treatment is required to prevent further morbidity and mortality specially in visceral and thoracic injuries. Therefore, it is useful to raise awareness for preventing this type of injury so as to cause less public health burden. Asian Journal of Medical Sciences Vol.8(5) 2017 36-40